Cultural security evaluating the power of culture in international affairs - Nemeth, Erik (Imperial College Press insurgency and terrorism series, 2015)
Over the past two centuries, abuse of antiquities and fine art has evolved from the "spoils of war" into a medium for conducting terrorism which strives to erase the cultural heritage of "the other". At the same time, the growth of the art market over the past fifty years has created opportunities for exploitation of cultural property. Since World War II, there has been maturing international awareness